ANALISA BANGKITAN PERJALANAN PADA PERUMAHAN KORPRI LOA BAKUNG DI KOTA SAMARINDA - MARDA, AGUS (KURVA S JURNAL MAHASISWA, 2020)
Residential area causing changes in land use functions which later cause problems, community activities to engage in activities lead to trip generation that can burden the road network paths to activity centers. Problems that occur in the residential area of Loa Bakung Korpri have the following problem formulation: 1. How is the rise of the trip model at the Loa Bakung Korpri Housing. 2. How is the R2 Test Result on the generation at the Loa Bakung Korpri Housing. For data that corresponds to the problem under study, the researcher uses data collection techniques to disseminate 167 questionnaire sheets and by interviewing the family is done in order to get direct information about the questionnaire in the questionnaire and in the data processing the analyst using a SPSS software with double regression analysis. From the data on the Housing Loa Bakung Korpri population there are 3 RT 57, RT 67, RT 71 and the number of Residents is 286 Family Heads. The results of the data obtained from the questionnaire contained 4 Modeling of Movement Generations namely Monthly Income (X3), the purpose of the trip =0,189 (X4),the reason for vehicle users= 0,087 (X7), Gasoline Costs =0,737. Departure time to destination (X9) =0,120 So the dependent variable that is formed is Y (trip awakening). Of the 4 models, the regression equation Y = -0,379+ 0.189 (X3) + 0.087 (X4) + 0.737 (X7) + 0.120 (X9) 2 Shows the levels of the relationship of the dependent variable (Bound Variable) with the Independent variable (the independent variable) at the level of strong correlation The mathematical model of trip generation above states that out of the total of fourteen independent variables (X) there are four variables selected that have a high degree of correlation and has a significant relationship to the dependent variable (Y)